EXTRACTION OF BIOACTIVE COMPOUNDS FROM SARGASSUM SP. AND THEIR BIOACTIVE POTENTIAL OF CYTOTOXICITY AND HEMOLYTIC ACTIVITIES. - Tanmayi Mishra, Dr. Abirami Arthanari (Chelonian Research Foundation, 2023)
INTRODUCTION: Seaweed from shallow maritime meadows, sargassum species are brown macroalgae from tropical and subtropical regions. These are a wholesome and abundant supply of bioactive substances, including vitamins, carotenoids, dietary fibers, proteins, and minerals. Additionally, a variety of Sargassum species were used to isolate a number of biologically active substances, including terpenoids. Numerous biological effects, including analgesic, anti-inflammatory, antioxidant, neuroprotective, anti-microbial, anti-tumor, fibrinolytic, immune-modulatory, anti-coagulant, hepatoprotective, and antiviral activity, are displayed by these isolated compounds. AIM: The aim of the study is to evaluate cytotoxic and hemolytic activity of Sargassum. MATERIALS AND METHODS: Preparation of the crude extract was done. Followed by the cytotoxic and hemolytic assay of the Sargassum sp using MTT assay. RESULTS: When we compare the cytotoxic activity of Sargassum in different concentration, we find that at higher concentration the cell viability is the least. When we compare the hemolytic activity of Sargassum at different concentrations we find that, at higher concentration the hemolysis is the highest. DISCUSSION: Various researches have been done for cytotoxicity and hemolytic activity using natural and alternative compounds, Hep2 cell lines, in vitex stimulated digestive actions, sugars, etc. CONCLUSION: Sargassum species can be used for their cytotoxic activity and hemolytic activity and can be used for further medical researches. KEYWORDS: Sargassum sp, cytotoxic activity, hemolytic activity, assay, in vitro.